Contributions of Carlos Rafael Rodríguez to the evolution of the notion of economic development in Cuba (Islas, 2021)
The notion of economic development and its evolution has been approached by schools of economic thought, and from all ideological currents. Cuba has not been the exception; it has been actively present in all stages of the national history. Carlos Rafael Rodríguez is a reference point for the Marxist approach of the aforementioned topic. His active bibliography is studied from historical materialism, in addition, the logical-abstract and analysis-synthesis methods, as well as triangulation are applied. We analyze his work, without encomiums; exposing his contributions to the process of evolution of the notion of economic development in Cuba, and recognizing the validity of his legacy, 108 years after his birth.
Keywords: notion; economic development; evolution; Carlos Rafael Rodríguez